Kinetic equation having the integral scattering term with a linear form of external electrical and magnetic fields - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
In many cases, nobody considers any kinetic equation where the collision integral does not clearly use the values of external electric and magnetic fields. But there is some reason to use in the collision integral the above fields and to consider the ratio of the averaged de Broglie wavelength to the free-path length. У багатьох випадках при розгляді кінетичного рівняння в інтегралі зіткнення даремно не враховується наявність зовнішніх електричних та магнітних полів у явному вигляді. Насправді існує певна причина уважно використовувати в інтегралі зіткнення вищезазначені поля і правильно оцінювати кінцеві результати, приймаючи відношення усередненої довжини хвилі де Бройля до середньої довжини вільного пробігу.